Substrate quality influences organic matter accumulation in the soil silt and clay fraction. (December 2016) - Cyle, K.T.; Hill, N.; Young, K.; Jenkins, T.; Hancock, D.; Schroeder, P.A.; Thompson, A.
Abstract: Substrate quality impacts the rate of microbial decomposition of soil organic matter (OM), with higher quality substrates leading to faster rates of decomposition. Since OM decomposition is the opposite of OM stabilization, one might presume higher quality substrates would lead to less OM stabilization. Yet, there is growing evidence that C stabilized in the soil silt and clay fractions is preferentially derived from microbial metabolites. We hypothesized that the decomposition of higher quality substrates would increase silt and clay-sized (S)OM pools despite higher initial mineralization rates. Soils low in initial organic carbon were incubated for 139 d with substrates spanning a range of quality/lability including: (a) bermudagrass forage cut after 14d, 21d, 28d, 35d, and 42d of re-growth, and (b) ruminal digesta produced from these forages. We then monitored the production of CO2 as well as the carbon abundance and isotopic composition in the bulk, silt, and clay fractions. Undigested forage was respired at higher initial rates than ruminal digesta and resulted in more carbon (C) and nitrogen (N) in the clay fraction. Overall, substrate quality—assessed as the ratio of neutral detergent fiber (NDF-cellulose, hemicellulose, and lignin) to crude protein (CP)—was directly related to decomposition kinetics with higher substrate quality resulting in more silt and clay C. These findings provide evidence that substrate quality, as a driver of microbial response, can control the flow of C and N to silt and clay fractions where there is the potential for interactions with mineral surfaces to greatly increase C and N residence times. Incorporating this concept into numerical models of SOM generation and turnover will likely improve projections of carbon dynamics in global change models. Highlights: Soil carbon mineralization dynamics were monitored after substrate additions. Soils receiving higher quality substrates had higher initial respiration rates. Increases in clay associated C were linked to faster decomposition kinetics.